Willingness of parents to vaccinate their 6-60-month-old children with EV71 vaccines: a cross-sectional study in rural areas of northern Jiangsu Province - Yuanyuan Wang; Fanyu Meng; Jingxin Li; Guifan Li; Jialei Hu; Jiaqian Cao; Qiufan Yu; Qi Liang; Fengcai Zhu (Taylor & Francis Group, 2020)
Enterovirus 71 (EV71) is the dominant pathogen in severe and fatal hand-foot-mouth disease (HFMD) cases. Since 2015, three inactivated EV71 vaccines have been approved in China. The vaccination coverage of the EV71 vaccine has been relatively low, especially in rural areas. A cross-sectional survey from July 19 to August 22, 2018, was conducted in three rural counties of northern Jiangsu Province among parents of children aged 6-60 months. We adopted a pretested validated questionnaire to assess knowledge, awareness, and attitude of HFMD and EV71 vaccines among respondents and used univariate and multivariate binary logistic analyses to explore potential factors associated with the acceptance of EV71 vaccines. Of the 1,112 parents who participated, 87.8% were willing to vaccinate their children with EV71 vaccines. Parents over 40 y old were less likely to have their children vaccinated [adjusted odds ratio (aOR) = 2.12, 95% conﬁdence interval (CI): 1.13-3.97]. Parents who lived in Ganyu (aOR = 0.50, 95% CI: 0.31-0.79) or Xinyi county (aOR = 0.33, 95% CI: 0.20-0.53), had a university or higher degree (aOR = 0.26, 95% CI: 0.11-0.64), had good knowledge of EV71 vaccines (aOR = 0.81, 95% CI: 0.67-0.98), perceived their children's disease susceptibility, and worried about the severity of HFMD had a higher willingness to vaccinate their children. Most parents were willing to vaccinate their children against EV71-related HFMD. Parental age, location, education level, knowledge of EV71 vaccines, concern about susceptibility, and severity of HFMD were all factors that influenced willingness to vaccinate.